The effect of urban-rail station area coverage on city blocks’ epidemic transmission: the case of the rail-supportive city of Beijing, China - Zhang, Weitao; Li, Jingwei (Frontiers in Public Health, 2025)
BackgroundFrom coronavirus disease 2019 (COVID-19) to other human-to-human infectious diseases, the integrative development of rail transport and land use, which is dominated by the theory of the transport–land use feedback cycle, concentrates citizens’ large-scale flow and gathering within the rail station areas (RSAs). This makes RSAs the potential “focal point” of epidemic spread in cities. This study examined the effect of RSA coverage on epidemic transmission in rail-supportive city blocks and further revealed the internal mechanism and potential factors behind the surface effect.Methods and resultsA quantitative empirical analysis was conducted using a typical COVID-19 case in Beijing, China, in 2020, and the statistical analysis method of “a mediating model with a moderating effect” was used, resulting in the following multilayered outcomes: (1) The higher the coverage, the lower the risk, overall, which is different from the general empiricism-based judgment. (2) Behind the total effect, RSA coverage does not directly affect epidemic transmission in blocks, as expected because of the focal point effect on epidemic occurrence possibility. Instead, RSA coverage has a mediating effect on epidemic vulnerability by affecting the residential population size of blocks. (3) There is a strengthening effect on RSA coverage affecting the population size as RSA transport and service levels increase.ConclusionThese findings have several implications. First, the implementation of contemporary local nonpharmaceutical interventions can be considered to reduce the focal point effect of RSAs and decrease the infectious sensitivity of the block population. Second, the transport–land use integration plays a key role behind the mediating and moderating effects by shaping resident land use and population distribution. Third, the blocks’ primary hospitals, advanced hospitals, municipal roads, and elastic facilities probably provide potential support in reducing blocks’ epidemic risk.